Comparative analysis of pubertal growth spurt predictors: Martins and Sakima method and Grave and Brown method - Iguma,Karina Emy (2005)
The aim of this study was to evaluate whether Martins and Sakima and Grave and Brown methods are useful for the study of pubertal growth spurt in children with cleft lip and palate. A total of 132 hand-wrist radiographs of patients from HRAC/USP aged 7 to 17 years old were analyzed, including girls and boys. Six radiographs of each age and gender were employed. These methods were applied to evaluating the stages of the hand-wrist ossification and epiphyseal formation, by graphic representation. The Martins and Sakima and the Grave and Brown methods revealed that the initial, peak and final stages of pubertal growth spurt occurred between 9 to 10, 12 and 15 years old, respectively, in the female gender. Similarly, in the male gender, both Martins and Sakima and Grave and Brown methods showed similar mean ages: 12, 14 and 16 years old for initial, peak and final stages of pubertal growth spurt, respectively. The Pearson's correlation test showed high and significant correlation (r = 0.99 and p < 0.001) between the methods investigated. In conclusion, the methods appeared to be highly and significantly correlated as regards the analysis of children with cleft lip and palate. Moreover, based on the literature and present results, it is possible to suggest that the two methods have shown similar pattern and may be used with equal efficiency for assessment of the pubertal growth spurt in children with cleft lip and palate.